Pengembangan Modul Praktikum Digital Berbasis Web Pada Materi Perencanaan Pengalamatan Jaringan - Setyawan, Antonius Edy; Tuah, Yayan Adrianova Eka; Angon, Apolosius (Universitas Negeri Gorontalo, 2025)
This study aims to develop a web-based digital practicum module for Network Addressing Planning (PPJ) material at SMK Budi Luhur Sintang-West Kalimantan. The problem faced is the lack of use of technology in practicum learning, especially in PPJ material. For this reason, module development is carried out which allows students to learn independently and interactively. The method used is development research (Research and Development) with the 4D model, which includes defining, designing, developing, and disseminating stages. The results showed that this module was feasible to use based on the feasibility test from material experts with a score of 54 (good category) and media experts with a score of 59 (very good category), as well as positive responses from students and teachers. The small group trial with 10 students resulted in 72.6% positive response (decent category), while the large group trial with 30 students resulted in 95.7% positive response (very decent category). This module succeeded in improving the quality of learning by providing a more interesting learning experience and facilitating the understanding of technical concepts independently. The conclusion of this study is that the development of a web-based digital practicum module can improve the quality of learning PPJ material at SMK Budi Luhur Sintang..